2006
DOI: 10.1158/0008-5472.can-05-4589
|View full text |Cite
|
Sign up to set email alerts
|

Protein Disulfide Isomerase Expression Is Related to the Invasive Properties of Malignant Glioma

Abstract: By serial transplantation of human glioblastoma biopsies into the brain of immunodeficient nude rats, two different tumor phenotypes were obtained. Initially, the transplanted xenografts displayed a highly invasive phenotype that showed no signs of angiogenesis. By serial transplantation in animals, the tumors changed to a less invasive, predominantly angiogenic phenotype. To identify novel proteins related to the invasive phenotype, the xenografts were analyzed using a global proteomics approach. One of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
181
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(187 citation statements)
references
References 30 publications
4
181
0
2
Order By: Relevance
“…The 1st generation tumors did not exhibit contrast enhancement indicating intact vessel structures as previously described. 24,25 As in the patients, the addition of a contrast agent revealed a hyper-intense area in the high generation tumors indicating a compromised blood-brain-barrier (BBB) (Fig. 1b).…”
Section: Cd133 Expression Coincides With Onset Of Tumor Angiogenesis mentioning
confidence: 80%
See 2 more Smart Citations
“…The 1st generation tumors did not exhibit contrast enhancement indicating intact vessel structures as previously described. 24,25 As in the patients, the addition of a contrast agent revealed a hyper-intense area in the high generation tumors indicating a compromised blood-brain-barrier (BBB) (Fig. 1b).…”
Section: Cd133 Expression Coincides With Onset Of Tumor Angiogenesis mentioning
confidence: 80%
“…22 Furthermore, it has recently been demonstrated that CD133 negative cells from human glioblastoma multiforme (GBM) exhibit cancer stem cell properties as well, although their proliferation index was lower than for CD133 positive cells. 23 Thus, the role of CD133 positive cells versus other cell populations in brain tumor initiation and progression is still uncertain.We have previously developed a human glioma model by implanting human GBM biopsy spheroids into the brains of nude rats, 24,25 and showed that these tumors express a number of stem cell markers. 24 The establishment of naive human GBM biopsy material into a host of a different species (rat), and the expression of primitive cell markers, indicate a high cellular adaptability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the antigens, the human ortholog of PDI manifested immunogenicity in a limited number of cancer patients, whereas the closely related disulfide isomerase ERp5 elicited humoral reactions that were temporally associated with clinically significant anti-tumor effects in 4 different solid and hematologic malignancies. Because ERp5 facilitates immune escape through the enhancement of MICA shedding 53 and may also promote tumor cell invasion through modifying surface thiols, 56,57 our results raise the possibility that this disulfide isomerase may be a useful target for cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 80%
“…The mechanism involved in these diseases states include suppression of apoptosis by PDI which results in the progression of tumor growth and metastasis. Cell surface PDI is also implicated in cancer progression and administering anti-PDI monoclonal antibodies inhibits the invasion of glioma cells [70] . This further validates that PDI promotes survival and progression of various forms of cancer cells.…”
Section: Pdi In Cancermentioning
confidence: 99%